If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -2) = 72 Reorder the terms: 9(-2 + x) = 72 (-2 * 9 + x * 9) = 72 (-18 + 9x) = 72 Solving -18 + 9x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 9x = 72 + 18 Combine like terms: -18 + 18 = 0 0 + 9x = 72 + 18 9x = 72 + 18 Combine like terms: 72 + 18 = 90 9x = 90 Divide each side by '9'. x = 10 Simplifying x = 10
| 3(2x-5)+6=4x+7 | | 4(x-3)=x-5 | | 5d+15-2d-10=11 | | 256+5546=x | | 8+3x=-4x+57 | | 4x+3(4x-6)=110 | | -3+4x=4(x-7)+25 | | -6x+8y=-22 | | -4x-1=-4-7x | | 5d+15-2d-10=10 | | 7x-4=6+6x | | 3x+6(x+8)=129 | | 4(t-3)=25 | | X-5=3(2x-1) | | 5s+4c=46 | | 3e+038= | | -7x+3=x-13 | | 5+y=2x | | -34-3x=-8x+46 | | 5x+2(5x-11)=128 | | -3+-8n=5 | | 3.5r=147 | | 4y+1=2y-8 | | 57=19 | | -18=-84x | | y=100-25x | | 3x+5(3x+9)=135 | | -2(i+6)+3=-11i+4(i+4) | | x-3=12x-7 | | 10+5x=4x+11 | | y=x^2+6x-14 | | -25=-7y+3 |